Correlation between Multiple Intelligence and English Academic Performance of EFL Learners of 11th Grade Students Senior High School - Lidia Gusnen Mimid; Kasmaini Kasmaini; Elfrida Elfrida (Universitas Bengkulu, 2020)
The main purpose of this study was to review intelligence types that students employ in relation to their foreign language learning. This correlational study aimed to investigate the correlation of multiple intelligences and students’ academic performance. The population of this study was 205 student’s 11th grade of senior high school of 03 SELUMA. The data was collected by using total sampling learning English class eleventh senior high school. Data analyzed this study of to investigate the correlation between the multiple intelligences and the academic achievement score of senior high school students. Data was analyzed by descriptive statistics the results from Pearson Correlation of intelligence and academic achievement variables. Based on the data analysis it was found between two variables was 0.348, results showed that low correlation existed between multiple intelligences and academic performance. As a consequence, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. This indicates that multiple intelligences did not significantly affect academic performance. It seems that multiple intelligences were not the only factor that affects the achievement. Intrapersonal the leading intelligence type and the musical intelligence was the least common intelligence type employed by the students who participated in this research.